METODE DEMONSTRASI UNTUK PENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN FIQIH DI MI ULUMUDDIN GUDO JOMBANG - Mustofa, Ali; Fiqruddin, Ahmad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The background of this research is the author's attention to the teaching and learning process of fourth grade students at MI Ulumuddin in the Fiqh subject, there are still many students who seem to lack understanding and enthusiasm in participating in each learning process, thus affecting student learning outcomes in learning. The purpose of this study was to find out: the application of the demonstration method in learning, and improving student learning outcomes at MI Ulumuddin Gudo Jombang in the academic year. This research is a type of field research (field reserch). Researchers used data collection techniques through observation, interviews with school principals, grade IV teachers, and grade IV students and through documentation. The data analysis technique used is by means of data reduction, data presentation, and verification. The results of the study show: First, the application of the demonstration method to the Fiqh, namely the initial stage is for the teacher to make a lesson plan. The second stage is the process of applying the demonstration method. The third stage is assessment with the teacher giving assignments to students. The steps for implementing the demonstration method are the teacher giving greetings and greetings to students, then the teacher conveys the learning objectives, then the teacher explains the prayer material to students, after that the teacher practices the material in front of the class, after practicing the teacher appoints one of the students to demonstrate the material that has been taught. explained with their friends, after the students demonstrated the teacher gave conclusions or evaluations and gave assignments in the student book related to prayer material. This method can overcome the monotony of students and make students active in the lesson.